Evidence of Bovine viral diarrhea virus Infection in Three Species of Sympatric Wild Ungulates in Nevada: Life History Strategies May Maintain Endemic Infections in Wild Populations - Wolff, Peregrine L.; Schroeder, Cody; McAdoo, Caleb; Cox, Mike; Nelson, Danielle D.; Evermann, James F.; Ridpath, Julia F. (Frontiers in Microbiology, 2016)
Evidence for bovine viral diarrhea virus (BVDV) infection was detected in 2009-10 while investigating a pneumonia die-off in Rocky Mountain bighorn sheep (Ovis canadensis canadensis), and sympatric mountain goats (Oreamnos americanum) in adjacent mountain ranges in Elko County, Nevada. Seroprevalence to BVDV-1 was 81% (N=32) in the bighorns and 100% (N=3) in the mountain goats. Serosurveillance from 2011 to 2015 of surviving bighorns and mountain goats as well as sympatric mule deer (Odocoileus hemionus), indicated a prevalence of 72% (N=45), 45% (N=51), and 51% (N=342) respectively. All species had antibody titers to BVDV1 and BVDV2. BVDV1 was isolated in cell culture from three bighorn sheep and a mountain goat kid. BVDV2 was isolated from two mule deer. Six deer (N=96) sampled in 2013 were positive for BVDV by antigen-capture ELISA on ear notch. Wild ungulates and cattle concurrently graze public and private lands in these two mountain ranges, thus providing potential for interspecies viral transmission. Like cattle, mule deer, mountain goats, and bighorn sheep can be infected with BVDV and can develop clinical disease including immunosuppression. Winter migration patterns that increase densities and species interaction during the first and second trimester of gestation may contribute to the long term maintenance of the virus in these wild ungulates. More studies are needed to determine the population level impacts of BVDV infection on these three species.